EPID-22. NEWLY-DIAGNOSED BRAIN TUMORS IN PEDIATRIC PATIENTS: EPIDEMIOLOGY IN THE UNITED STATES. (11th November 2019) - Torre, Matthew; Ascha, Mustafa; Harary, Maya; Smith, Timothy; Aizer, Ayal; Ligon, Keith; Reardon, David; Barnholtz-Sloan, Jill; Iorgulescu, Bryan
Abstract: INTRODUCTION: Herein we examine the epidemiology across all pediatric intracranial tumors in the U.S. METHODS: Pediatric patients (< 20yo) presenting between 2010–2015 with an intracranial tumor as the first evidence of cancer were queried from the National Cancer Database, which comprises >70% of cancers newly-diagnosed in the U.S. Tumor types were classified by WHO2016 ICD-O3. RESULTS: 14, 952 pediatric patients without a history of cancer presented with intracranial tumors between 2010–2015. Across all ages, these were comprised of 1) 22% diffuse astrocytic and oligodendroglial (n=3, 328), 2) 17% sellar region (n=2, 530), 3) 16% other astrocytic (n=2, 378, 2, 131 were pilocytic and pilomyxoid), 4) 13% embryonal (n=1, 896; 1, 092 were classic histology medulloblastomas), 5) 7% neuronal and mixed neuronal-glial (n=981), 6) 5% ependymal (n=752), 7) 4% GCTs (n=615), 8) 3% mesenchymal non-meningothelial (n=492), 9) 3% nerve sheath (n=428), and 10) ≤2% each of meningioma, choroid plexus, brain metastatic (44% from neuroblastoma), pineal region, hematologic, and other glioma tumors. Embryonal tumors predominated in neonates and infants (0-2yo), diffuse gliomas in childhood (3-11yo), and sellar tumors in adolescents (12-19yo). Females represented 49% of the cases, but sellar tumors predominated (23%, vs. only 11% in males); whereas in males diffuse gliomas predominated (23%; vs. 22% in females) overall and in pediatric patients older than 2yo. CONCLUSIONS: In U.S. pediatric patients that present with a new intracranial tumor, embryonal tumors and diffuse gliomas predominate in infants ≤2yo, and continue to predominate in male children 3-11yo, whereas female children 3-11yo shifted towards a predominance by diffuse gliomas and other astrocytic tumors (e.g. pilocytic and pilomyxoid). In female adolescents 12-19yo, sellar tumors predominated, followed by diffuse gliomas; whereas in male adolescents diffuse gliomas predominated, followed by other astrocytic tumors and sellar tumors. Our findings demonstrate that newly-diagnosed intracranial masses in pediatric patients significantly vary by both age and sex.